2019
DOI: 10.1111/jace.16469
|View full text |Cite
|
Sign up to set email alerts
|

Highly enhanced thermoelectric performance in BiCuSeO ceramics realized by Pb doping and introducing Cu deficiencies

Abstract: In recent years, BiCuSeO oxyselenides have been developed as a promising thermoelectric material. In this article, PbxBi1−xCu1−ySeO (x = y = 0, 0.02, 0.04, 0.06, and 0.08) are prepared by solid‐state reaction method and spark plasma sintering (SPS), and the combinatorial effects of Pb doping and Cu deficiencies on thermoelectric properties are investigated systematically. The transport properties are significantly enhanced due to the optimized carrier density, majorly contributing to the promotion of ZT values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…However, our results indicate that for the oxyselenide-based compounds, which are intrinsically anisotropic, layered materials, taking anisotropy into account is essential even for the pressed polycrystalline samples. It can be suggested that the observed anisotropy in the thermal conductivity is mainly related to a preferential grain growth perpendicular to the applied pressure direction during the SPS process (see Figures S11−S13), which is in a good accord with the literature data 52 and was confirmed by SEM studies (Figure S12). Hereinafter, only measurements carried out in the perpendicular direction are presented.…”
Section: ■ Computational Detailssupporting
confidence: 87%
See 1 more Smart Citation
“…However, our results indicate that for the oxyselenide-based compounds, which are intrinsically anisotropic, layered materials, taking anisotropy into account is essential even for the pressed polycrystalline samples. It can be suggested that the observed anisotropy in the thermal conductivity is mainly related to a preferential grain growth perpendicular to the applied pressure direction during the SPS process (see Figures S11−S13), which is in a good accord with the literature data 52 and was confirmed by SEM studies (Figure S12). Hereinafter, only measurements carried out in the perpendicular direction are presented.…”
Section: ■ Computational Detailssupporting
confidence: 87%
“…Moreover, the carrier concentration of all the samples increased with increasing temperature due to the thermal excitation. The charge carrier density in BiCuSeO may be affected by various crystal defects, such as anti-site defects, 50 deviations from nominal oxidation states, 44,51 or vacancies 47,52 as it was previously reported for oxychalcogenide-based compounds. 53−56 Although the role of defects in this system requires further detailed studies, it is clear that the enhanced electrical conductivity of the BM BiCuSeO and that of the substituted samples should be attributed to the increased charge carrier density (see Table 3).…”
Section: ■ Computational Detailsmentioning
confidence: 72%
“…S1 (ESI †), the main reason for such a significant enhancement of the electrical conductivity is due to the increase in the charge carrier concentration, which is also in agreement with previous reports. 22,24 Furthermore, the carrier density increase originates mostly from the substitution of Bi 3+ with Pb 2+ , as even introducing only dual vacancies V Bi and V Cu in BiCuSeO led to an order of magnitude lower conductivity in comparison with the Pb-substituted ones. 12 Nonetheless, as discussed in the Introduction section, the introduction of vacancies plays not a primary but a complementary role, leading to a more pronounced delocalization of charge carriers between the layers, thereby promoting interlayer charge transfer.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, metal oxides have been widely researched in the thermoelectric field due to their good thermal stability, earth abundance, and nontoxicity. ,, Zinc oxide (ZnO) has been widely researched for several decades owing to its particular properties, namely, its wide direct band gap (3.37 eV), asymmetric hexagonal c -axis crystal structure, sensitive surface reaction, and good thermal stability. Due to these superior properties, ZnO has been applied in UV photodetectors, piezoelectric devices, gas sensors, and thermoelectric devices. , In a recent study on the thermoelectric application of undoped ZnO films, the superlattice structure and oxidant type were varied to increase the TE performance. ,, Alshareef et al discussed the thermoelectric properties of two kinds of treated ZnO films .…”
Section: Introductionmentioning
confidence: 99%